Accelerating shear-induced crystallization and enhancing crystal orientation of isotactic-polypropylene via nucleating agent self-assembly. (5th December 2018) - Chang, Baobao; Schneider, Konrad; Lu, Bo; Vogel, Roland; Zheng, Guoqiang; Heinrich, Gert
Abstract: Accelerating shear-induced crystallization and enhancing crystal orientation of isotactic-polypropylene (iPP) via controlling the morphology of N, N′-dicyclohexyl-2, 6-naphthalene dicarboxamide (NJS) is reported here. By adjusting the final heating temperature, NJS crystallizes into dotlike, needlelike, and treelike morphologies. Due to the selective absorption, longer polymer chains are anchored on the surface of NJS, leading to a lower viscosity of the composite than pure iPP. Since that anchoring points will inhibit the relaxation of oriented polymer chains after shear ceases, the shear-induced crystallization kinetics of the composite is greatly accelerated compared with pure iPP. As the morphology of NJS changes from dotlike to treelike, the crystallization induction time decreases further from 620 s to 250 s. Additionally, the branches of the treelike NJS will be detached from the tree upon the shear flow and orient themselves in the shear direction, which endows a highest degree of crystal orientation of the composites with treelike NJS. Graphical abstract: Highlights: Due to the selective absorption, longer polymer chains are anchored on the surface of NJS. The anchoring points inhibit the relaxation of polymer chains, which accelerate greatly the crystallization kinetics. The detachment and orientation of NJS branches from the tree upon shear flow benefits the crystal orientation.